Effects of exogenous hydrogen sulphide on calcium signalling, background (TASK) K channel activity and mitochondrial function in chemoreceptor cells - Buckler, K (2012)
It has been proposed that endogenous H2S mediates oxygen sensing in chemoreceptors; this study investigates the mechanisms by which H 2S excites carotid body type 1 cells. H2S caused a rapid reversible increase in intracellular calcium with EC50≈6 μM. This [Ca2+]i response was abolished in Ca-free Tyrode. In perforated patch current clamp recordings, H2S depolarised type 1 cells from -59 to -35 mV; this was accompanied by a robust increase in [Ca 2+]i. Voltage clamping at the resting membrane potential abolished the H2S-induced rise in [Ca2+]i. H2S inhibited background K+current in whole cell perforated patch and reduced background K+ channel activity in cell-attached patch recordings. It is concluded that H2S excites type 1 cells through the inhibition of background (TASK) potassium channels leading to membrane depolarisation and voltage-gated Ca2+ entry. These effects mimic those of hypoxia. H2S also inhibited mitochondrial function over a similar concentration range as assessed by NADH autofluorescence and measurement of intracellular magnesium (an index of decline in MgATP). Cyanide inhibited background K channels to a similar extent to H2S and prevented H2S exerting any further influence over channel activity. These data indicate that the effects of H2S on background K channels are a consequence of inhibition of oxidative phosphorylation. Whilst this does not preclude a role for endogenous H2S in oxygen sensing via the inhibition of cytochrome oxidase, the levels of H2S required raise questions as to the viability of such a mechanism. © Springer-Verlag 2012.